THE ROLE OF ARTIFICIAL INTELLIGENCE PROGRAMS IN DISTANCE EDUCATION FOR FITNESS AND SPORTS - ‍Nagorna Viktoriia; Mytko, Artur; Petrenko, Hennadii; Shutova, Svitlana (Sworld-Us Conference proceedings, 2023)
Digital media has become an integral part of our lives, including the lives of children and youth. With the rapid advancement of technology, it is essential to explore how digital media can be effectively integrated into education, particularly in the fie